Video art a guided tour - Elwes, Catherine 1952- (I.B. Tauris, 2006)
Video art dominates the international art world to such an extent that its heady days on the radical fringes are sometimes overlooked - often unknown. The book is an essential and highly entertaining guide to video art and its history.